(untitled) (The International Journal for Scientific Research, 2023)
The study focused on Abu Amr Al-Basri’s substitution of the silent hamza (hamza saakin) and explored the following inquiries: - Who was the source of Abu Amr’s account regarding the substitution of the silent hamza? - What locations are exempted from the silent hamza substitution? How many are there, and what justifies their exemption? - Did Abu Amr himself narrate the exceptions for these locations, or was it a decision made by Ibn Mujahid? The investigation revealed the following findings: - Abu Amr received the account of the silent hamza substitution from his mentor, Abu Jaafar Yazid bin Al-Qaqa. Additionally, he acquired similar information from other mentors regarding the clarification of the silent hamza (Tahqeeq Al-Hamza Al-Saakin(. - The consensus on the exemption applied to fifteen words in thirty five locations. - There are five meanings and reasons justifying the exemption of these locations, elaborated in the study. - All these exempted locations were narrated directly from Abu Amr Ibn Mujahid’s selection of these exceptions implies his preference for the specifically delimited narration from Abu Amr, as opposed to an unrestricted narration without exceptions, which also exists in Abu Amr’s accounts.